Genetic Polymorphism of IFNA1 and IFNAR1 Genes in Covid-19 Iraqi Patients - A. Almukhtar, Asmaa; M. Ali, Amal; A. Mahmood, Noah (Al-Nahrain Journal of Science, 2023)
Coronavirus disease 2019 (Covid-19) is a deadly acute respiratory illness brought on by an infection with coronavirus 2. (SARS-CoV-2). The severity of the syndrome was variant among the individuals ranging between severe and mild. Interferons type 1 are one of the cytokines inactive the viral replication. Genetic variation in rs2850015 for IFNA1 and rs202055606 for IFNAR1 were investigated by high-resolution melting analysis. Results showed that TT genotype and T allele of rs202055606 polymorphism represented a significant positive odds ratio as risk factor for severity while C allele act as protective factor. The rs2850015 polymorphism revealed conversion T to G, the GG genotype and G allele represented a significant positive odds ratio as risk factor for severity while the T allele represent protective factor from severity. It was be concluded that the GG genotype and G allele for rs2850015 and TT genotype and T allele may be associated with severity of Covid-19.